PERBANDINGAN RASIO KEUANGAN PADA PERUSAHAAN SUB SEKTOR LOGAM DAN SEJENISNYA 2018-2022 - Marbawi, Darlis; Malahayati, Rina; Natanael, Yunita Althin (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2024)
This research aims to look at the comparison of financial ratios in metal and similar sub-sector companies for 2018-2022 using analysis of liquidity ratios, solvency ratios, profitability ratios and efficiency ratios. This research is quantitative descriptive in nature and the research population in the research is 18 companies in the metals and similar sub-sector companies which were studied for 5 years from 2018-2022. The data collection technique used is census. The results of this research are firstly that the liquidity ratios of all companies experienced an increase from year to year, while none experienced a decrease from year to year. Second, the solvency ratio for companies in the metal and similar sub-sectors is only JKSW which has increased from year to year. The profitability ratio that experienced a decline from year to year was INAI while the others experienced ups and downs and there were no efficiency ratios that experienced increases and decreases from year to year. Keywords: finalcial ratios, liquidity, solvency, profitability, efficiency